Ordered arrays of Au catalysts by FIB assisted heterogeneous dewetting. (17th November 2015) - Benkouider, A; Ronda, A; David, T; Favre, L; Abbarchi, M; Naffouti, M; Osmond, J; Delobbe, A; Sudraud, P; Berbezier, I
Abstract: Synthesizing Au0.8 Si0.2 nanocatalysts that are homogeneous in size and have controlled position is becoming a challenging and crucial prequisite for the fabrication of ordered semiconductor nanowires. In this study, Au0.8 Si0.2 nanocatalysts are synthesized via dewetting of Au layers on Si(111) during thermal annealing in an ultra-high vacuum. In the first part of the paper, the mechanism of homogeneous dewetting is analyzed as a function of the Au-deposited thickness ( h Au ). We distinguish three different dewetting regimes: (I) for a low thickness ( ), a submonolyer coverage of Au is stabilized and there is no dewetting. (II) For an intermediate thickness ( ), there is both dewetting and Au0.8 Si0.2 phase formation. The size and density of the Au0.8 Si0.2 clusters are directly related to h Au . When cooling down to room temperature, the clusters decompose and reject the Si at the Au/Si substrate interface. (III) For a large thickness ( ), only dewetting takes place, without forming AuSi clusters. In this regime, the dewetting is kinetically controlled by the self-diffusion of Au (activation energy ∼0.43 eV) without evidence of an Si-alloying effect. As a practical consequence, when relying solely on the homogeneous dewetting of Au/Si(111) to form the Au0.8 Si0.2 catalysts (without a supply of Si atoms from vapor), regime II should be used to obtain good size and density control. In the second part of the paper, a process for ordering the catalysts using focused ion beam-(FIB) assisted dewetting (heterogeneous dewetting) is developed. We show that no matter what the FIB milling conditions and the Au nominal thickness are, dewetting is promoted by ion beam irradiation and is accompanied by the formation of Au0.8 Si0.2 droplets. The droplets preferentially form on the patterned areas, while in similar annealing conditions, they do not form on the unpatterned areas. This behavior is attributed to the larger Au-Si interdiffusion in the patterned areas, which results from the Si amorphization induced by the FIB. A systematic analysis of the position of the nanodroplets shows their preferential nucleation inside the patterns, while thicker platelets of almost pure Au are observed between the patterns. The evolutions of the size homogeneity and the occupancy rate of the patterns are quantified as a function of the FIB dose and annealing temperature. Nice arrays of perfectly ordered AuSi catalysts are obtained after optimizing the FIB and dewetting conditions.